Functional analysis of a first hindlimb positioning enhancer via Gdf11 expression - Saito, Seiji; Kanazawa, Utsugi; Tatsumi, Ayana; Iida, Atsuo; Takemoto, Tatsuya; Suzuki, Takayuki (Frontiers in Cell and Developmental Biology, 2024)
During the early development of tetrapods, including humans, the embryonic body elongates caudally once the anterior-posterior axis is established. During this process, region-specific vertebral morphogenesis occurs, with the determination of limb positioning along the anterior-posterior axis. We previously reported that Gdf11 functions as an anatomical integration system that determines the positioning of hind limbs and sacral vertebrae where Gdf11 is expressed. However, the molecular mechanisms underlying induction of Gdf11 expression remain unclear. In this study, we searched for non-coding regions near the Gdf11 locus that were conserved across species to elucidate the regulatory mechanisms of Gdf11 expression. We identified an enhancer of the Gdf11 gene in intron 1 and named it highly conserved region (HCR). In HCR knockout mice, the expression level of endogenous Gdf11 was decreased, and the position of the sacral-hindlimb unit was shifted posteriorly. We also searched for factors upstream of Gdf11 based on the predicted transcription factor-binding sites within the HCR. We found that inhibition of FGF signaling increased endogenous Gdf11 expression, suggesting that FGF signaling negatively regulates Gdf11 expression. However, FGF signaling does not regulate HCR activity. Our results suggest that there are species-specific Gdf11 enhancers other than HCR and that FGF signaling regulates Gdf11 expression independent of HCR.